Myxedema crisis in an adolescent girl, successfully treated by oral thyroxine: A case report - Rahul Tandon; Amit Kumar; Shradha Patel; Sandip Mori; Fenil Thakkar; Krutika Tandon (Wolters Kluwer Medknow Publications, 2023)
Myxedema crisis is a condition with high mortality. It affects adults more often than children. Patients present with low blood pressure, low pulse, low body temperature, hypoventilation, and gastrointestinal dysfunction. Here, we present a case report of a teenage girl who was diagnosed with acquired hypothyroidism at the age of 7 years and was effectively treated with oral thyroxine in myxedema crisis.